Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Layanan Expedisi - Ahmad Zhofaro Jawharul Fadl; Halimah Zahrah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The growth of the logistics sector driven by the expansion of e-commerce has intensified competition in the delivery service industry. Under these conditions, price and service quality play an important role in shaping customer satisfaction. This study aims to examine the effect of price and service quality on customer satisfaction with the Special Express Mail service at the Bandung Post Office. A quantitative approach with a survey method was employed, involving users selected through purposive sampling. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed using multiple linear regression. The findings indicate that price and service quality have a positive influence on customer satisfaction, both partially and simultaneously, with service quality playing a more dominant role. Therefore, continuous improvement in service quality and the implementation of fair and competitive pricing strategies are essential to enhance customer satisfaction and maintain competitiveness in the delivery service industry.